2005
DOI: 10.1177/0143831x05051519
|View full text |Cite
|
Sign up to set email alerts
|

Confronting a Changing Economy: Union Responses in Finland

Abstract: This article looks at the economic and social changes confronting trade unions in Finland, and how the unions are responding to these changes. The original empirical research comprises a sample of 12 unions, and the interviews with union leaders, officials and trustees focus on the societal changes and the ensuing union responses from the interviewees’ own experience and point of view. Finland has seen a change from strike-prone unionism towards labour–management cooperation that extends the limits of a single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…In both countries, unions responded with official strikes, walkouts, work to rule, and overtime bans during the 1980s and 1990s in an attempt to protect public sector employment and better wages (Stokke and Thornqvist, 2002). But by the late 1990s and early 2000s, fearing higher unemployment, wage-push inflation, and European Union competition, unions sought to bring an end to wildcat strikes in order to focus on centralized negotiations intended to lower unemployment (Kalliola, 2005). In the public sector, these have meant increased workloads as well as more part-time and temporary employment, especially for women in education, healthcare, and social services (Elvander, 2002).…”
Section: The Limits Of Government Partisanship Unions and Corporatismmentioning
confidence: 99%
See 1 more Smart Citation
“…In both countries, unions responded with official strikes, walkouts, work to rule, and overtime bans during the 1980s and 1990s in an attempt to protect public sector employment and better wages (Stokke and Thornqvist, 2002). But by the late 1990s and early 2000s, fearing higher unemployment, wage-push inflation, and European Union competition, unions sought to bring an end to wildcat strikes in order to focus on centralized negotiations intended to lower unemployment (Kalliola, 2005). In the public sector, these have meant increased workloads as well as more part-time and temporary employment, especially for women in education, healthcare, and social services (Elvander, 2002).…”
Section: The Limits Of Government Partisanship Unions and Corporatismmentioning
confidence: 99%
“…Others backed away from militancy, fearing that strikes would further undercut public support or that wage gains would only increase deficits and subsequently hike interest rates, setting off further problems through the continued introduction of austerity measures. At the same time, to ensure this defensive strategy, union leadership reined in militancy, strikes, and public campaigns over the past two decades (Kalliola, 2005;Piazza, 2005;Scheuer, 2006;Upchurch et al, 2009). This was the case in Canada, the United States, and the United Kingdom, as well as Germany and Finland.…”
Section: The Limits Of Government Partisanship Unions and Corporatismmentioning
confidence: 99%
“…Firm pressures for differentiated collective agreements divided unions internally, pitting better paid workers against part-time and younger workers over wages, hours, and job security, and many unions discovered that their memberships no long longer believed that their unions were working for the interests of all (Kalliola, 2005;Standing, 2002). In addition, firm efforts to achieve 'competitiveness' have led many unions to shift their collective bargaining goals towards ensuring firm success and cash flows, rather than improving wages and work conditions.…”
Section: The Loss Of Labour Powermentioning
confidence: 99%
“…In addition to drawing from Denmark' s experience of being more strategic, Canadian unions can look to Finland which also has a high rate of density. Kalliola' s (2005) research of Finnish unions' responses to social and economic changes reveals that these unions engaged in modernization strategies and greater labour-management cooperation to ensure long-term job security and viability. Multi-professional teamwork is a process where unions work together to form new alliances, often through mergers (Kalliola, 53 2005).…”
Section: Section 44 Revitalization Strategy #4: Broaden Appealmentioning
confidence: 99%
“…Multi-professional teamwork is a process where unions work together to form new alliances, often through mergers (Kalliola, 53 2005). The research of Finnish labour unions revealed four areas where unions are concentrating their efforts: job security, maintenance of collective bargaining, ability to influence social legislation and labour law, and revamping the organization of unions (Kalliola, 2005). Canadian unions can use this type of approach as well , by narrowing their focus of activity and effort.…”
Section: Section 44 Revitalization Strategy #4: Broaden Appealmentioning
confidence: 99%